Investigation of diffusional transport of heat and its enhancement in phase-change thermal energy storage systems. (25th January 2017) - Saraswat, Amit; Bhattacharjee, Rajdeep; Verma, Ankit; Das, Malay K.; Khandekar, Sameer
Abstract: Thermal energy storage in general, and phase-change materials (PCMs) in particular, have been a major topic of research for the last thirty years. Due to their favorable thermo-dynamical characteristics, such as high density, specific heat and latent heat of fusion, PCMs are usually employed as working fluids for thermal storage. However, low thermal conductivities of organic PCMs have posed a continuous challenge in its large scale deployment. This study focuses on experimental and numerical investigation of the melting process of industrial grade paraffin wax inside a semi-cylindrical enclosure with a heating strip attached axially along the center of semi-cylinder. During the first part of the study, the solid-liquid interface location, the liquid flow patterns in the melt pool, and the spatial and temporal variation of PCM temperature were recorded. For numerical simulation of the system, open source library OpenFOAM® was used in order to solve the coupled Navier-Stokes and energy equations in the considered system. It is seen that the enthalpy-porosity technique implemented on OpenFOAM® is reasonably well suited for handling melting/solidification problems and can be employed for system level design. Next, to overcome the inherent thermal limitations of PCM storage material, the study further explored the potential of coupling the existing heat source with copper-water heat pipes, so as to help augment the rate of heat dissipation within the medium by increasing the effective system-level thermal conductivity. Integration of heat pipes led to enhanced transport, and hence, a substantial decrease in the total required melting time. The study provides a framework for designing of large systems with integration of heat pipes with PCM based thermal storage systems.